Fiber-reinforced 3D printing lightweight high-strength concrete and preparation method thereof
By adding modified carbon fiber and lightweight fillers to 3D printed lightweight concrete, and using toughened microsphere particles to form a network structure, the problem of early shrinkage and cracking of concrete is solved, and its tensile strength and compressive strength are significantly improved. and durability performance.
Patent Information
- Application Number
- CN202411344188.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-21
AI Technical Summary
Existing 3D printed lightweight concrete is prone to early shrinkage and cracking during the preparation process, resulting in a decrease in the corrosion resistance and permeability of the structure, affecting its strength and overall stability.
Using fiber reinforcement, modified carbon fibers and lightweight fillers are added to the concrete, and toughened microsphere particles are used to improve the toughness of the fibers and the viscosity of the concrete to form a network structure to resist cracking and fracture.
It significantly improves the tensile strength and cracking performance of 3D printed concrete, reduces the risk of interlayer peeling and cracking, and improves the compressive strength and durability of concrete.
Smart Images

Figure BDA0005060504840000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and more specifically, to a fiber-reinforced 3D printed lightweight high-strength concrete and a preparation method thereof. Background Art
[0002] The acceleration of urbanization and industrialization requires the support of science and technology. The shortage of skilled labor, resource depletion, safety issues, etc. have seriously restricted the development of the construction industry. The development of 3D printing technology has provided new ideas for researchers and engineers in the construction industry. It has the sample principle of a two-dimensional printer, and can stack the printed planes layer by layer to obtain a three-dimensional design model. Construction 3D printing technology can reduce construction waste, reduce labor costs and improve production efficiency. Therefore, it is of great significance to study the application of lightweight and high-strength concrete suitable for construction 3D printing in the field of civil engineering.
[0003] In the construction industry, lightweight high-strength concrete has many advantages, such as significantly reducing the static load of the structure, reducing the cost of the superstructure and foundation, good thermal insulation and sound insulation performance, and reducing building energy consumption. Lightweight high-strength cement-based materials are multi-purpose building materials with technical, economic and environmental advantages and broad application prospects. Therefore, the development of a new type of 3D printed lightweight high-strength concrete has important practical significance.
[0004] At present, the preparation of 3D printed lightweight concrete mainly uses lightweight materials such as ceramsite to achieve the purpose of reducing the weight of concrete. However, when the amount of lightweight materials such as ceramsite is too much, the compressive strength of concrete will decrease. In addition, for 3D printed concrete, in order to obtain good construction performance, 3D printed concrete usually has the characteristics of fast setting and early strength, which makes the early shrinkage of the material develop faster and is prone to early shrinkage cracking. In addition, since 3D printed concrete is always exposed to the air during the layer-by-layer stacking process, without the use of formwork enclosure, the water evaporates and loses rapidly, causing the material to shrink faster and increase the risk of early cracking of the material. When shrinkage cracks appear after 3D printing concrete, the cracks will have a serious adverse effect on the corrosion resistance of the 3D printed concrete structure, including sulfate erosion resistance, chloride ion erosion resistance and impermeability, and may even damage the strength and overall stability of the 3D printed concrete structure, causing economic losses that cannot be ignored and even safety issues.
[0005] Therefore, selecting effective technical measures to regulate the shrinkage cracking performance of 3D printed concrete, preparing lightweight and high-strength concrete, and reducing and avoiding cracking caused by shrinkage in 3D printed concrete are of great significance for the promotion and application of 3D concrete. Summary of the invention
[0006] In order to obtain lightweight and high-strength concrete while improving the cracking performance of 3D printed concrete, the present application provides a fiber-reinforced 3D printed lightweight and high-strength concrete and a preparation method thereof.
[0007] In the first aspect, the present application provides a fiber-reinforced 3D printed lightweight high-strength concrete, which adopts the following technical solution: A fiber-reinforced 3D printed lightweight high-strength concrete, comprising the following raw materials in parts by weight: 600-800 parts of cement, 50-120 parts of silica fume, 200-300 parts of sand, 150-200 parts of water, 8-12 parts of admixture, 50-100 parts of modified fiber and 150-250 parts of lightweight filler; The lightweight filler is made of expanded perlite and EPS particles in a mass ratio of 1:(2-3); The modified fiber at least includes modified carbon fiber, which is prepared from carbon fiber, toughening microspheres and adhesive in a mass ratio of 1: (0.4-0.5): (0.2-0.4), and the toughening microspheres are prepared by dipping nano silicon dioxide in a mixed solution of γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane, drying the solution and then mixing the solution with a monomer mixture, wherein the monomer mixture is prepared by mixing an acrylate monomer, a styrene monomer, an initiator, a crosslinking agent, a surfactant, a stabilizer and water.
[0008] By adopting the above technical scheme, in the present application, lightweight fillers are added to cement-based materials to reduce the mass of concrete and obtain lightweight concrete. In addition, modified carbon fibers are added to the present application, and toughened microsphere particles are formed on the surface of the modified carbon fibers through an adhesive. The toughened microsphere particles play a better role in energy absorption and stress dispersion when the concrete is subjected to tensile or bending stress, thereby slowing down the fracture process of the carbon fibers and improving their crack resistance. Moreover, the toughened microsphere particles protruding from the fibers further improve the viscosity between the concrete base materials through mechanical bite between the fibers. The adhesive can also further enhance the bonding performance between the concrete base materials. The 3D printed concrete finally obtained has excellent tensile strength and cracking performance. During the 3D printing process, these fibers can be evenly distributed as the concrete is stacked layer by layer, thereby forming a network structure inside the concrete. When the concrete is subjected to external loads, the fibers can effectively resist the cracking and fracture of the concrete. Moreover, the toughening effect of the fibers can improve the bonding strength of the printed layer, reduce the risk of interlayer delamination and cracking, and improve the crack resistance and toughness of the concrete. In addition, the toughened microsphere particles on the carbon fiber of the present application are based on nano-silica as the skeleton structure, and then dispersed and immersed in a mixed solution to which γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane are added. After the addition of γ-methacryloxypropyltrimethoxysilane, the alkoxy groups on it are hydrolyzed and react with the silanol groups on the surface of the silica, thereby introducing the γ-methacryloxypropyltrimethoxysilane to the surface of the silica to achieve the introduction of unsaturated double bonds. The addition of γ-aminopropyltriethoxysilane introduces amino groups on the surface of the silica, and then after the monomer mixture is added, Under the action of the initiator, the unsaturated double bonds in the acrylate monomer and the styrene monomer are polymerized with the unsaturated double bonds in the γ-methacryloxypropyltrimethoxysilane on the surface of the nano-silica, realizing polymerization on the silica skeleton structure. The obtained composite toughened microspheres have a more excellent toughening effect. In addition, the introduction of silane groups on the nano-silica helps to improve the compatibility and bonding performance of the toughened microspheres with carbon fibers and inorganic substances in the concrete base material. The nano-silica skeleton structure also helps to improve the compressive strength of the concrete, and finally a 3D printed concrete with better mechanical properties and durability is obtained.
[0009] Optionally, the toughened microspheres are prepared by the following method: 1) Add γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane to water to obtain a mixed solution, then add nano-silica, disperse evenly, immerse for 30-60 minutes, and dry to obtain modified nano-silica microspheres; 2) Add the modified nano-silica microspheres prepared in step 1) into water, then add the monomer mixture, polymerize at 80-90° C. for 2-3 hours, stop the reaction, cool, filter, and wash with water to obtain toughened microspheres; Wherein, in step 1), the mass concentration of γ-methacryloxypropyltrimethoxysilane in the mixed solution is 30-40wt%, the mass concentration of γ-aminopropyltriethoxysilane in the mixed solution is 15-20wt%, and the mass ratio of the mixed solution to the nano-silicon dioxide is 10:(0.4-0.6); In step 2), the added mass ratio of the modified nano-silica microspheres to water is 1:(10-12), and the added mass of the monomer mixture is 2-4 times the mass of the modified nano-silica microspheres.
[0010] By adopting the above technical solution and controlling the above addition amount and polymerization time, the polymerization degree and molecular chain length based on the nano-silica skeleton can be controlled to prevent the particle size of the nano-silica from being increased too much due to excessive polymerization, which in turn reduces the toughening effect.
[0011] Optionally, the specific operation of aggregation in step 2) is: First, polymerize at 80-90° C. for 60-90 min, then add polylactic acid, and then continue the reaction polymerization, wherein the amount of polylactic acid added is 3-5wt% of the modified nano-silica microspheres.
[0012] By adopting the above technical scheme, when primary polymerization is realized in the polymerization process in the present application, after adding polylactic acid, the hydroxyl functional group in the polylactic acid reacts with the amino group in γ-aminopropyltriethoxysilane on the nano-silica, and the polylactic acid can also form a chemical connection with the silane part in γ-methacryloxypropyltrimethoxysilane to form a graft polymerization, so that polylactic acid is introduced into the primary macromolecule formed in the polymerization process, and the network structure formed by interlacing significantly improves the strength of the modified carbon fiber. The toughened microspheres on the carbon fiber significantly improve the crack resistance and the compressive strength. In addition, the introduction of polylactic acid on the modified carbon fiber can also react with cement gel, thereby promoting the development of early strength of concrete, helping to improve the compressive strength of concrete, and finally obtaining lightweight and high-strength concrete while significantly improving the crack resistance of 3D printed concrete.
[0013] Optionally, the nano-silicon dioxide in the toughened microspheres is prepared by the following method: Water glass is added into water to prepare a silicic acid solution with a mass concentration of 30-40%, and then an acid agent, aluminum nitrate and cerium nitrate are added, and the pH is adjusted to 3.5-5. After stirring, the solution is allowed to stand, filtered, and then dried and calcined to prepare nano-silicon dioxide loaded with aluminum and cerium, wherein the added mass ratio of aluminum nitrate, cerium nitrate and water glass is 1: (0.4-0.6): (30-40).
[0014] By adopting the above technical scheme, when the nano-silica in the present application is selected to be loaded with aluminum and cerium elements, it is found that the introduction of aluminum elements can react with cement slurry to generate aluminates, thereby reducing the pore structure inside the concrete, which helps to improve the compressive strength and corrosion resistance of the concrete, and the introduction of cerium elements can promote the hardening of cement, making the concrete denser, and improve the strength of the concrete by improving the strength and crystal structure of the hardened material, and can also reduce the chloride ion permeability of the concrete and improve the durability of the concrete. Finally, it is found that the selection of nano-silica doped with aluminum and cerium elements can significantly improve the strength and corrosion resistance of the concrete.
[0015] Optionally, when preparing nano-silicon dioxide, the specific calcination operation is: first heat to 280-320°C and heat for 1-1.5h, then heat to 450-500°C and heat for 2-4h, then heat to 780-850°C and keep warm for 1-3h before cooling to room temperature, and ball milling to obtain nano-silicon dioxide.
[0016] By adopting the above technical scheme, wet silica gel loaded with aluminum and cerium elements is prepared under strong acidic conditions, and then after the above high-temperature calcination treatment, nano-scale silicon dioxide with a porous structure is obtained, which can achieve excellent toughening effect.
[0017] Optionally, each raw material in the monomer mixture is added according to the following weight parts: 40-50 parts of acrylate monomer, 20-30 parts of styrene monomer, 3-5 parts of initiator, 5-10 parts of crosslinking agent, 5-10 parts of surfactant and 5-10 parts of stabilizer and 120-150 parts of water; The acrylate monomer is selected from one or more of ethyl acrylate, butyl acrylate, methyl methacrylate, lauryl methacrylate, 2-ethylhexyl acrylate, ethoxyethyl acrylate, and ethyl acetoacetate methacrylate; the crosslinking agent is selected from one or more of ethylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,3-butanediol dimethacrylate, and 1,6-hexanediol diacrylate; The surfactant is selected from one or both of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; The stabilizer is selected from one or both of polyvinyl alcohol and polyvinyl pyrrolidone.
[0018] Optionally, the modified fiber comprises modified carbon fiber and glass fiber in a mass ratio of 1:(0.5-0.7).
[0019] By adopting the above technical scheme, glass fiber is also added to the modified fiber. The high-strength and high-modulus glass fiber can significantly improve the compressive strength of concrete, and at the same time significantly improve the crack resistance of concrete. In addition, the glass fiber contains hydroxyl and silane functional groups. The glass fiber reacts with the amino group introduced on the modified carbon fiber and the carboxyl group on the polylactic acid through the hydroxyl group, and the introduction of the silane group further improves the compatibility of the carbon fiber, the glass fiber and the matrix, realizes the connection between the glass fiber and the carbon fiber, further forms a network structure, further improves the compressive strength and crack resistance of the concrete, and finally obtains 3D printed concrete with better comprehensive mechanical properties and durability.
[0020] Optionally, the glass fiber is prepared by modifying polyvinyl chloride chips, and the specific operation is as follows: The glass fiber is first pretreated by soaking in hydrofluoric acid for 30-90 seconds, then washed and dried to obtain pretreated glass fiber; the polyvinyl chloride mastic is heated to 120-130°C, and after heating for 20-30 minutes, polyvinyl chloride slices and stabilizer are added, and the temperature is raised to 160-170°C and heated to a molten state to obtain a modifier, and then the molten modifier is coated on the surface of the glass fiber to obtain an initial modified glass fiber, and then the initial modified glass fiber is cooled to room temperature within 10-20 minutes to solidify to obtain a modified glass fiber.
[0021] By adopting the above technical scheme, the glass fiber is first pre-treated by immersion in hydrofluoric acid to remove surface impurities, and then coated with a molten mixture of polyvinyl chloride slices and polyvinyl chloride putty. The polyvinyl chloride putty is used as a polyvinyl chloride adhesive to achieve the bonding of polyvinyl chloride on the glass fiber, and then solidified to form a polyvinyl chloride coating, thereby improving the toughness and chemical corrosion resistance of the glass fiber, and also improving the strength and stiffness of the glass fiber, further improving the mechanical properties and durability of the final 3D printed concrete.
[0022] Optionally, during the glass fiber modification process, the amount of polyvinyl chloride putty added is 2-4wt% of the polyvinyl chloride slices, the amount of stabilizer added is 3-5wt% of the polyvinyl chloride slices, and the ratio of the polyvinyl chloride slices to the pretreated glass fiber added is 1:(5-8).
[0023] Optionally, the sand is gold tailings sand; the admixture includes a polycarboxylic acid water reducer and an accelerator in a mass ratio of 1:(1.2-1.5).
[0024] By adopting the above technical solution, the addition of accelerators in 3D printed concrete can prompt the cement particles to quickly hydrate and solidify, achieving sufficient strength in a short time to support the construction of subsequent printing layers.
[0025] In a second aspect, the present application provides a method for preparing fiber-reinforced 3D printed lightweight high-strength concrete, using the following technical solution: A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete, comprising the following steps: Mixing cement, silica fume and sand to prepare mixture A; Mixing water and an admixture to prepare a mixture B; Mixture A is mixed with a lightweight filler, and then the modified fiber is added and stirred, and then mixture B is added and stirred to obtain concrete.
[0026] By adopting the above technical solution, the method provided by the present application is simple and convenient and easy to realize industrialization.
[0027] In summary, this application has the following beneficial effects: 1. In the present application, the modified carbon fiber is formed with toughening microsphere particles on its surface by an adhesive. The toughening microsphere particles not only improve the toughness of the carbon fiber, but also the toughening microsphere particles protruding from the fiber further improve the viscosity between the concrete base materials through mechanical bite between the fibers. The adhesive can also further enhance the bonding performance between the concrete base materials. The prepared modified carbon fiber has excellent tensile strength and toughness. During the 3D printing process, these fibers can be evenly distributed as the concrete is stacked layer by layer, thereby forming a network structure inside the concrete. When the concrete is subjected to external loads, the fibers can effectively resist cracking and fracture of the concrete, thereby improving the crack resistance and toughness of the concrete. 2. The toughened microspheres in this application use nano-silica as the skeleton structure, and the unsaturated double bonds in the surface γ-methacryloxypropyltrimethoxysilane are polymerized with the monomer mixture on the silica skeleton structure. The obtained composite toughened microspheres have a more excellent toughening effect, and the introduction of silane groups on the nano-silica helps to improve the compatibility and bonding performance of the toughened microspheres with carbon fibers and inorganic substances in the concrete base material. The nano-silica skeleton structure also helps to improve the compressive strength of the concrete, and finally obtain 3D printed concrete with better mechanical properties and durability. 3. In the present application, when primary polymerization is realized during the polymerization process, after adding polylactic acid, the hydroxyl functional group in polylactic acid reacts with the amino group in γ-aminopropyltriethoxysilane on nano-silica, and polylactic acid can also form a chemical connection with the silane part in γ-methacryloxypropyltrimethoxysilane to form a graft polymerization, so that polylactic acid is introduced into the primary macromolecule formed during the polymerization process, and the network structure formed by interlacing significantly improves the strength of the modified carbon fiber. The toughened microspheres on the carbon fiber significantly improve the crack resistance and the compressive strength. In addition, the introduction of polylactic acid on the modified carbon fiber can also react with cement gel, thereby promoting the development of early strength of concrete, helping to improve the compressive strength of concrete, and finally obtaining lightweight and high-strength concrete while significantly improving the crack resistance of 3D printed concrete; 4. When the nano-silica in the present application is loaded with aluminum and cerium, it is found that the introduction of aluminum can react with cement slurry to form aluminate, thereby reducing the pore structure inside the concrete, which helps to improve the compressive strength and corrosion resistance of the concrete. The introduction of cerium can promote the hardening of cement, making the concrete denser, and improve the strength of the concrete by increasing the strength and crystal structure of the hardened material. It can also reduce the chloride ion permeability of the concrete and improve the durability of the concrete. Finally, it is found that the use of nano-silica doped with aluminum and cerium can significantly improve the strength and corrosion resistance of the concrete. DETAILED DESCRIPTION
[0028] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0029] In this application, cement used is P·O 42.5 ordinary Portland cement; The water reducer is polycarboxylate water reducer, the sand is gold tailings sand, and the accelerator is the cement accelerator produced by Shandong Juxian Jiangshan Technology Co., Ltd.
[0030] The following preparation example is an example of the preparation of toughened microspheres Preparation Example 1 A method for preparing toughened microspheres comprises the following steps: 1) Using 1 kg of nano-silica as the treatment standard, add γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane to water to obtain a mixed solution, then add nano-silica, disperse evenly, immerse for 40 minutes, and dry to obtain modified nano-silica microspheres; The mass concentration of γ-methacryloxypropyltrimethoxysilane in the mixed solution is 35wt%, the mass concentration of γ-aminopropyltriethoxysilane in the mixed solution is 20wt%, and the added mass ratio of the mixed solution to the nano-silicon dioxide is 10:0.5; 2) Mix 45 kg of acrylate monomer, 25 kg of styrene monomer, 4 kg of initiator, 8 kg of crosslinking agent, 8 kg of surfactant, 8 kg of stabilizer and 130 kg of water to prepare a monomer mixture; The modified nano-silica microspheres prepared in step 1) are added into water, and then the monomer mixture is added, and after polymerization at 85° C. for 2.5 hours, the reaction is stopped, and the mixture is cooled, filtered, and washed with water to obtain toughened microspheres; The added mass ratio of the modified nano-silica microspheres to water is 1:11, and the added mass of the monomer mixture is 3 times the mass of the modified nano-silica microspheres; In the monomer mixture, the acrylate monomer is ethyl acrylate and ethoxyethyl acrylate in a mass ratio of 1:1; the crosslinking agent is ethylene glycol dimethacrylate; the surfactant is sodium dodecyl sulfate; the stabilizer is polyvinyl pyrrolidone, and the initiator is benzoyl peroxide.
[0031] Preparation Example 2 A method for preparing toughened microspheres comprises the following steps: 1) Using 1 kg of nano-silica as the treatment standard, add γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane into water to obtain a mixed solution, then add nano-silica, disperse evenly, immerse for 30 minutes, and dry to obtain modified nano-silica microspheres; The mass concentration of γ-methacryloxypropyltrimethoxysilane in the mixed solution is 30wt%, the mass concentration of γ-aminopropyltriethoxysilane in the mixed solution is 15wt%, and the mass ratio of the mixed solution to the nano-silicon dioxide is 10:0.4; 2) Mix 40 kg of acrylate monomer, 20 kg of styrene monomer, 3 kg of initiator, 5 kg of crosslinking agent, 5 kg of surfactant, 5 kg of stabilizer and 120 kg of water to prepare a monomer mixture; The modified nano-silica microspheres prepared in step 1) are added into water, and then the monomer mixture is added, and after polymerization at 80° C. for 3 hours, the reaction is stopped, and the mixture is cooled, filtered, and washed with water to obtain toughened microspheres; The added mass ratio of the modified nano-silica microspheres to water is 1:10, and the added mass of the monomer mixture is twice the mass of the modified nano-silica microspheres; In the monomer mixture, the acrylate monomer is methyl methacrylate and lauryl methacrylate in a mass ratio of 1:1; the crosslinking agent is 1,6-hexanediol diacrylate; the surfactant is sodium dodecylbenzene sulfonate; the stabilizer is polyvinyl alcohol, and the initiator is benzoyl peroxide.
[0032] Preparation Example 3 A method for preparing toughened microspheres comprises the following steps: 1) Using 1 kg of nano-silica as the treatment standard, add γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane to water to obtain a mixed solution, then add nano-silica, disperse evenly, immerse for 60 minutes, and dry to obtain modified nano-silica microspheres; The mass concentration of γ-methacryloxypropyltrimethoxysilane in the mixed solution is 40wt%, the mass concentration of γ-aminopropyltriethoxysilane in the mixed solution is 20wt%, and the mass ratio of the mixed solution to the nano-silicon dioxide is 10:0.6; 2) Mix 50 kg of acrylate monomer, 30 kg of styrene monomer, 5 kg of initiator, 10 kg of crosslinking agent, 10 kg of surfactant, 10 kg of stabilizer and 150 kg of water to prepare a monomer mixture; The modified nano-silica microspheres prepared in step 1) are added into water, and then the monomer mixture is added, and after polymerization at 90° C. for 2 hours, the reaction is stopped, and the mixture is cooled, filtered, and washed with water to obtain toughened microspheres; The added mass ratio of the modified nano-silica microspheres to water is 1:12, and the added mass of the monomer mixture is 4 times the mass of the modified nano-silica microspheres; In the monomer mixture, the acrylate monomer is 2-ethylhexyl acrylate; the crosslinking agent is trimethylolpropane triacrylate; the surfactant is sodium dodecyl sulfate; the stabilizer is polyvinyl pyrrolidone, and the initiator is benzoyl peroxide.
[0033] Preparation Example 4 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 1, except that polylactic acid is added during polymerization at 85° C. in step 2). The specific operation is as follows: First, after polymerization at 85° C. for 60 min, polylactic acid was added, and then the polymerization was continued for 1.5 min and then the reaction was stopped, wherein the amount of polylactic acid added was 3 wt % of the modified nano-silica microspheres.
[0034] Preparation Example 5 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 1, except that polylactic acid is added during polymerization at 85° C. in step 2). The specific operation is as follows: First, polymerization was carried out at 85° C. for 90 min, and then polylactic acid was added, and then the polymerization was continued for 1 min and then the reaction was stopped, wherein the amount of polylactic acid added was 5 wt % of the modified nano-silica microspheres.
[0035] Preparation Example 6 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 4, except that the nano-silicon dioxide in step 1) is nano-silicon dioxide loaded with aluminum and cerium, which is specifically prepared by the following method: Water glass is added into water to prepare a silicic acid solution with a mass concentration of 35%, and then nitric acid, aluminum nitrate and cerium nitrate are added, the pH is adjusted to 4, stirred and then allowed to stand, filtered, and then dried and calcined. The specific calcination parameters are: first heated to 300°C for 1.5h, then heated to 480°C for 3h, then heated to 800°C and kept warm for 2h before cooling to room temperature. Nano-silicon dioxide loaded with aluminum and cerium with a particle size of 30-50nm is obtained by ball milling, wherein the added mass ratio of aluminum nitrate, cerium nitrate and water glass is 1:0.5:35.
[0036] Preparation Example 7 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 4, except that the nano-silicon dioxide in step 1) is nano-silicon dioxide loaded with aluminum and cerium, which is specifically prepared by the following method: Water glass is added into water to prepare a silicic acid solution with a mass concentration of 30%, and then nitric acid, aluminum nitrate and cerium nitrate are added, the pH is adjusted to 3.5, stirred and then allowed to stand, filtered, and then dried and calcined. The specific calcination parameters are: first heated to 280°C for 1.5h, then heated to 450°C for 4h, then heated to 780°C and kept warm for 3h before cooling to room temperature, and ball milling is performed to obtain nano-silicon dioxide loaded with aluminum and cerium with a particle size of 30-50nm, wherein the added mass ratio of aluminum nitrate, cerium nitrate and water glass is 1:0.4:30.
[0037] Preparation Example 8 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 4, except that the nano-silicon dioxide in step 1) is nano-silicon dioxide loaded with aluminum and cerium, which is specifically prepared by the following method: Water glass is added into water to prepare a silicic acid solution with a mass concentration of 40%, and then nitric acid, aluminum nitrate and cerium nitrate are added, the pH is adjusted to 5, stirred and then allowed to stand, filtered, and then dried and calcined. The specific calcination parameters are: first heated to 320°C for 1 hour, then heated to 500°C for 2 hours, then heated to 850°C and kept warm for 1 hour before cooling to room temperature, and ball milling is performed to obtain nano-silicon dioxide loaded with aluminum and cerium with a particle size of 30-50nm, wherein the added mass ratio of aluminum nitrate, cerium nitrate and water glass is 1:0.6:40.
[0038] Comparative Preparation Example 1 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 1, except that no γ-aminopropyltriethoxysilane is added to the raw materials.
[0039] Comparative Preparation Example 2 A method for preparing toughened microspheres is carried out according to the method in Preparation Example 1, except that an equal amount of γ-methacryloxypropyltrimethoxysilane in the raw material is replaced by KH-560.
[0040] Example 1 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete, comprising the following steps: S1, 700kg cement, 80kg silica fume and 250kg sand were mixed to prepare mixture A; S2, 180 kg of water and 10 kg of admixture are mixed to prepare mixture B; S3. Mix the mixture A prepared in step S1 with 200 kg of lightweight filler, then add 70 kg of modified fiber and stir, then add the mixture B prepared in step S2 and stir to obtain 3D printing concrete.
[0041] The admixture in step S2 is a polycarboxylate water reducer and an accelerator in a mass ratio of 1:1.3, the lightweight filler in step S3 is expanded perlite and EPS particles in a mass ratio of 1:2.5, and the modified fiber is modified carbon fiber and glass fiber in a mass ratio of 1:0.6; The modified carbon fiber is prepared from carbon fiber with a mass ratio of 1:0.4:0.3, the toughened microspheres prepared in Preparation Example 1, and the epoxy resin adhesive. The specific operation is as follows: first, the epoxy resin adhesive (the selected model is NPEL-128 epoxy resin, which is sourced from Wanqing Chemical Technology Co., Ltd.) is evenly applied on the surface of the carbon fiber, and then the toughened microspheres prepared in Preparation Example 1 are evenly sprinkled on the surface of the carbon fiber coated with the adhesive, and the modified carbon fiber is obtained by pressing and fixing and then drying.
[0042] Example 2 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete, comprising the following steps: S1, 600 kg of cement, 50 kg of silica fume and 200 kg of sand were mixed to prepare mixture A; S2, 150 kg of water and 8 kg of admixture are mixed to prepare mixture B; S3. Mix the mixture A prepared in step S1 with 150 kg of lightweight filler, then add 50 kg of modified fiber and stir, then add the mixture B prepared in step S2 and stir to prepare 3D printing concrete.
[0043] The admixture in step S2 is a polycarboxylate water reducer and an accelerator in a mass ratio of 1:1.2, the lightweight filler in step S3 is expanded perlite and EPS particles in a mass ratio of 1:2, and the modified fiber is modified carbon fiber and glass fiber in a mass ratio of 1:0.5; The modified carbon fiber is prepared from carbon fiber with a mass ratio of 1:0.4:0.2, toughened microspheres prepared in Preparation Example 2, and epoxy resin adhesive. The specific operation is as follows: first, the epoxy resin adhesive (the selected model is NPEL-128 epoxy resin, which is sourced from Wanqing Chemical Technology Co., Ltd.) is evenly applied on the surface of the carbon fiber, and then the toughened microspheres prepared in Preparation Example 2 are evenly sprinkled on the surface of the carbon fiber coated with the adhesive, and the modified carbon fiber is obtained by pressing and fixing and then drying.
[0044] Example 3 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete, comprising the following steps: S1, 800 kg of cement, 120 kg of silica fume and 300 kg of sand were mixed to prepare mixture A; S2, 200 kg of water and 12 kg of admixture were mixed to prepare mixture B; S3. Mix the mixture A prepared in step S1 with 250 kg of lightweight filler, then add 80 kg of modified fiber and stir, then add the mixture B prepared in step S2 and stir to prepare 3D printing concrete.
[0045] The admixture in step S2 is a polycarboxylate water reducer and an accelerator in a mass ratio of 1:1.5, the lightweight filler in step S3 is expanded perlite and EPS particles in a mass ratio of 1:3, and the modified fiber is modified carbon fiber and glass fiber in a mass ratio of 1:0.7; The modified carbon fiber is prepared from carbon fiber with a mass ratio of 1:0.5:0.4, toughened microspheres prepared in Preparation Example 3, and epoxy resin adhesive. The specific operation is as follows: first, the epoxy resin adhesive (the selected model is NPEL-128 epoxy resin, which is sourced from Wanqing Chemical Technology Co., Ltd.) is evenly applied on the surface of the carbon fiber, and then the toughened microspheres prepared in Preparation Example 3 are evenly sprinkled on the surface of the carbon fiber coated with the adhesive, and the modified carbon fiber is obtained by pressing and fixing and then drying.
[0046] Embodiment 4-8 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the toughening microspheres in the modified carbon fibers are the toughening microspheres prepared in 4-8 respectively.
[0047] Example 9 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that an equal amount of glass fiber is replaced by modified carbon fiber.
[0048] Example 10 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the glass fiber is prepared by modifying polyvinyl chloride slices. The specific operation is: The glass fiber is first pretreated by soaking in hydrofluoric acid for 60 seconds, then washed and dried to obtain the pretreated glass fiber; The polyvinyl chloride mastic is heated to 125°C, and after heating for 25 minutes, polyvinyl chloride chips and stabilizers are added, and the temperature is raised to 165°C and heated to a molten state to obtain a modifier, and then the molten modifier is coated on the surface of the glass fiber to obtain primary modified glass fiber, and then the primary modified glass fiber is cooled to room temperature within 15 minutes to solidify to obtain modified glass fiber.
[0049] The stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 1:1; During the glass fiber modification process, the amount of polyvinyl chloride putty added was 3wt% of the polyvinyl chloride slices, the amount of stabilizer added was 4wt% of the polyvinyl chloride slices, and the ratio of polyvinyl chloride slices to pretreated glass fiber added was 1:6.
[0050] Embodiment 11 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the glass fiber is prepared by modifying polyvinyl chloride slices. The specific operation is: The glass fiber is first pretreated by soaking in hydrofluoric acid for 30 seconds, then washed and dried to obtain the pretreated glass fiber; The polyvinyl chloride mastic is heated to 120°C, and after heating for 30 minutes, polyvinyl chloride chips and stabilizers are added, and the temperature is raised to 160°C and heated to a molten state to obtain a modifier, and then the molten modifier is coated on the surface of the glass fiber to obtain primary modified glass fiber, and then the primary modified glass fiber is cooled to room temperature within 10 minutes to solidify to obtain a modified glass fiber.
[0051] The stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 1:1; During the glass fiber modification process, the amount of polyvinyl chloride putty added was 2wt% of the polyvinyl chloride slices, the amount of stabilizer added was 3wt% of the polyvinyl chloride slices, and the ratio of polyvinyl chloride slices to pretreated glass fiber added was 1:5.
[0052] Example 12 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the glass fiber is prepared by modifying polyvinyl chloride slices. The specific operation is: The glass fiber is first pretreated by soaking in hydrofluoric acid for 90 seconds, then washed and dried to obtain the pretreated glass fiber; The polyvinyl chloride mastic is heated to 130°C, and after heating for 20 minutes, polyvinyl chloride chips and stabilizers are added, and the temperature is raised to 170°C, and heated to a molten state to obtain a modifier, and then the molten modifier is coated on the surface of the glass fiber to obtain primary modified glass fiber, and then the primary modified glass fiber is cooled to room temperature within 20 minutes to solidify to obtain a modified glass fiber.
[0053] The stabilizer is a mixture of calcium stearate and zinc stearate in a mass ratio of 1:1; During the glass fiber modification process, the amount of polyvinyl chloride putty added was 4wt% of the polyvinyl chloride slices, the amount of stabilizer added was 5wt% of the polyvinyl chloride slices, and the ratio of polyvinyl chloride slices to pretreated glass fiber added was 1:8.
[0054] Comparative Example 1-2 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the toughening microspheres in the modified carbon fiber are the toughening microspheres in Comparative Preparation Example 1 and Comparative Preparation Example 2, respectively.
[0055] Comparative Example 3 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the modified carbon fiber is replaced by carbon fiber and nano-silicon dioxide in equal amounts, and the mass ratio of carbon fiber to nano-silicon dioxide is 1:0.4.
[0056] Comparative Example 4 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the toughening microspheres in the modified carbon fiber are prepared by directly soaking nano-silicon dioxide in a styrene-acrylic emulsion (model S-01 styrene-acrylic emulsion of Shengda Chemical) for 1 hour and then drying, and the styrene-acrylic emulsion is 3 times the mass of nano-silicon dioxide.
[0057] Comparative Example 5 A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete is carried out according to the method in Example 1, except that the modified carbon fiber is directly replaced by carbon fiber in equal amounts.
[0058] Performance Testing The 3D printed concrete prepared in the examples and comparative examples of the present application was subjected to performance tests in accordance with the Technical Specification for 3D Printing of Concrete T / CECS786-2020. The initial setting time of the 3D printed concrete prepared in Examples 1-12 of the present application was within 15-25 minutes, the fluidity was between 170-185 mm, which met the fluidity and initial setting requirements, and the bulk density was between 1500-1600 kg / m 3 In order to meet the requirements of lightweight concrete, in order to consider the influence of fiber reinforcement and crack resistance, the 28d compressive strength, interlayer bond strength and crack resistance were also tested. Among them, the crack resistance was accelerated according to the crack resistance method in JC / T 951-2005 "Test method for crack resistance of cement mortar", and the initial cracking time was counted. The statistical results are shown in Table 1 below.
[0059] Table 1: Referring to the test results in Table 1 above, the 3D printed concrete prepared in this application has excellent 28d compressive strength. At the same time, the toughening effect of the fiber improves the bonding strength of the printed layer, reduces the risk of interlayer peeling and cracking, and the prepared 3D printed concrete also has excellent interlayer bonding strength and crack resistance, and has better mechanical properties and durability. Combining the test results of Example 1 with Examples 4 and 5, it can be seen that the addition of polylactic acid after the toughened microspheres are prepared and polymerized to form a primary small molecule structure not only helps to improve the compressive strength, but also helps to improve the interlayer bonding strength and crack resistance, and the formation of a larger macromolecular network structure helps to improve the bonding performance of concrete. Combined with the test results of Example 4 and Examples 6-8, nano-silica loaded with copper and cerium further improves the comprehensive performance of 3D printed concrete compared with ordinary nano-silica; combined with the test results of Example 1 and Example 9, it can be seen that the performance of concrete only with modified carbon fiber added is reduced compared with the addition of modified carbon fiber and glass fiber at the same time; combined with the test results of Example 1 and Examples 10-12, the addition of modified glass fiber can further improve the comprehensive performance of concrete.
[0060] Referring to the test results of Example 1 and Comparative Examples 1 and 2, when no amino group is introduced into the toughened microspheres in Comparative Example 1, the chemical connection between the modified carbon fiber and the glass fiber may be reduced. It can be seen that the compressive strength, bonding strength and crack resistance of the concrete are all reduced; when the unsaturated double bond silane agent on the surface of the nano-silicon dioxide is replaced with an ordinary silane coupling agent in Comparative Example 2, the comprehensive performance of the concrete is significantly reduced. Combined with the test results in Comparative Example 3, the carbon fiber and the nano-silicon dioxide are directly added without the toughening treatment in Example 1, and the interlayer bonding strength and crack resistance are significantly reduced. In Comparative Example 4, the nano-silicon dioxide is directly added after being immersed in a styrene-acrylic emulsion, and the comprehensive performance of the concrete is poor. Combined with the modified carbon fiber in Comparative Example 5, when the same amount of carbon fiber is directly replaced, the comprehensive performance of the concrete is significantly reduced.
[0061] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fiber-reinforced 3D printed lightweight high-strength concrete, characterized in that: It includes the following raw materials in parts by weight: 600-800 parts of cement, 50-120 parts of silica fume, 200-300 parts of sand, 150-200 parts of water, 8-12 parts of admixture, 50-80 parts of modified fiber and 150-250 parts of lightweight filler; The lightweight filler is made of expanded perlite and EPS particles in a mass ratio of 1:(2-3); The modified fiber at least includes modified carbon fiber, which is made of carbon fiber, toughening microspheres and adhesive in a mass ratio of 1: (0.4-0.5): (0.2-0.4); The toughened microspheres are prepared by dipping nano-silica in a mixed solution of γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane, drying the solution, and then mixing the solution with a monomer mixture. The monomer mixture is prepared by mixing acrylate monomers, styrene monomers, initiators, crosslinking agents, surfactants, stabilizers and water.
2. A fiber-reinforced 3D printed lightweight high-strength concrete according to claim 1, characterized in that: The toughened microspheres are prepared by the following method: 1) Add γ-methacryloxypropyltrimethoxysilane and γ-aminopropyltriethoxysilane to water to obtain a mixed solution, then add nano-silica, disperse evenly, immerse for 30-60 minutes, and dry to obtain modified nano-silica microspheres; 2) Add the modified nano-silica microspheres prepared in step 1) into water, then add the monomer mixture, polymerize at 80-90° C. for 2-3 hours, stop the reaction, cool, filter, and wash to obtain toughened microspheres; Wherein, in step 1), the mass concentration of γ-methacryloxypropyltrimethoxysilane in the mixed solution is 30-40wt%, the mass concentration of γ-aminopropyltriethoxysilane in the mixed solution is 15-20wt%, and the mass ratio of the mixed solution to the nano-silicon dioxide is 10:(0.4-0.6); In step 2), the added mass ratio of the modified nano-silica microspheres to water is 1:(10-12), and the added mass of the monomer mixture is 2-4 times the mass of the modified nano-silica microspheres.
3. A fiber-reinforced 3D printed lightweight high-strength concrete according to claim 2, characterized in that: The specific operations of aggregation in step 2) are: First, after polymerization at 80-90° C. for 60-90 min, polylactic acid is added, and then the polymerization reaction is continued, wherein the amount of polylactic acid added is 3-5wt% of the modified nano-silica microspheres.
4. The fiber-reinforced 3D printed lightweight high-strength concrete according to claim 1, characterized in that: The nano-silicon dioxide in the toughened microspheres is prepared by the following method: Water glass is added into water to prepare a silicic acid solution with a mass concentration of 30-40%, and then an acid, aluminum nitrate and cerium nitrate are added, and the pH is adjusted to 3.5-5. After stirring, the solution is allowed to stand, filtered, and then dried and calcined to prepare nano-silicon dioxide loaded with aluminum and cerium, wherein the added mass ratio of aluminum nitrate, cerium nitrate and water glass is 1: (0.4-0.6): (30-40).
5. The fiber-reinforced 3D printed lightweight high-strength concrete according to claim 1, characterized in that: The raw materials in the monomer mixture are added according to the following weight parts: 40-50 parts of acrylate monomer, 20-30 parts of styrene monomer, 3-5 parts of initiator, 5-10 parts of crosslinking agent, 5-10 parts of surfactant and 5-10 parts of stabilizer and 120-150 parts of water; The acrylate monomer is selected from one or more of ethyl acrylate, butyl acrylate, methyl methacrylate, lauryl methacrylate, 2-ethylhexyl acrylate, ethoxyethyl acrylate, and acetoacetoxyethyl methacrylate; The crosslinking agent is selected from one or more of ethylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,3-butanediol dimethacrylate, and 1,6-hexanediol diacrylate; The surfactant is selected from one or both of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; The stabilizer is selected from one or both of polyvinyl alcohol and polyvinyl pyrrolidone.
6. The fiber-reinforced 3D printed lightweight high-strength concrete according to claim 1, characterized in that: The modified fiber comprises modified carbon fiber and glass fiber in a mass ratio of 1:(0.5-0.7).
7. The fiber-reinforced 3D printed lightweight high-strength concrete according to claim 6, characterized in that: The glass fiber is prepared by modifying polyvinyl chloride chips, and the specific operation is as follows: The glass fiber is first pretreated by soaking it in hydrofluoric acid for 30-90 seconds, then washed and dried to obtain the pretreated glass fiber; The polyvinyl chloride mastic is heated to 120-130°C, and after heating for 20-30 minutes, polyvinyl chloride chips and stabilizers are added, and the temperature is raised to 160-170°C, and heated to a molten state to obtain a modifier, and then the molten modifier is coated on the surface of the glass fiber to obtain primary modified glass fiber, and then the primary modified glass fiber is cooled to room temperature within 10-20 minutes to solidify to obtain a modified glass fiber.
8. The fiber-reinforced 3D printed lightweight high-strength concrete according to claim 7, characterized in that: During the glass fiber modification process, the amount of polyvinyl chloride mortar added is 2-4wt% of the polyvinyl chloride slices, the amount of stabilizer added is 3-5wt% of the polyvinyl chloride slices, and the ratio of the polyvinyl chloride slices to the pretreated glass fiber is 1: (5-8).
9. The fiber-reinforced 3D printed lightweight high-strength concrete according to claim 1, characterized in that: The sand is gold tailings sand; the admixture includes a polycarboxylic acid water reducer and an accelerator in a mass ratio of 1: (1.2-1.5).
10. A method for preparing fiber-reinforced 3D printed lightweight high-strength concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: Mixing cement, silica fume and sand to prepare mixture A; Mixing water and an admixture to prepare a mixture B; Mixture A is mixed with a lightweight filler, and then the modified fiber is added and stirred, and then mixture B is added and stirred to obtain concrete.
Citation Information
Cited By
Bridge concrete for extremely cold areas
CN120698747A